112cx+3c+-12cx+7=

Simple and best practice solution for 112cx+3c+-12cx+7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 112cx+3c+-12cx+7= equation:


Simplifying
112cx + 3c + -12cx + 7 = 0

Reorder the terms:
7 + 3c + 112cx + -12cx = 0

Combine like terms: 112cx + -12cx = 100cx
7 + 3c + 100cx = 0

Solving
7 + 3c + 100cx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + 3c + -7 + 100cx = 0 + -7

Reorder the terms:
7 + -7 + 3c + 100cx = 0 + -7

Combine like terms: 7 + -7 = 0
0 + 3c + 100cx = 0 + -7
3c + 100cx = 0 + -7

Combine like terms: 0 + -7 = -7
3c + 100cx = -7

Reorder the terms:
7 + 3c + 100cx = -7 + 7

Combine like terms: -7 + 7 = 0
7 + 3c + 100cx = 0

The solution to this equation could not be determined.

See similar equations:

| 3(x+4)3(x-2)=0 | | -6t+4=34 | | -81bc+7bc= | | 16x-5=10x+19 | | 3x+12*3x-6=3 | | 3(x+4)3(x-2)=3 | | x^2+11x=28 | | 5[2x-7]=15x-10 | | c=ax+b | | 8xy-(x+2xy)+3x= | | 2(xy+2x)-3xy= | | 7x^4=21x^2 | | 8y-13x-8=4 | | -13xy+9y-9xy+18y= | | -xy+-9xy= | | 25ab-37ab= | | 3[x-2]=2x+6 | | 110-90= | | 50+60= | | 12a-14a=3 | | -4n-8/17=23 | | a+c/2x=b | | x^2+2x=37 | | 2[x+3]=x+10 | | 6(3.14)=3.14x | | 2x+6=x+10 | | 2/x=5/x-6 | | 211c=105 | | q+(-10)=2 | | (y/4)=-7 | | p-8/(1/2)=-3 | | 100g=20 |

Equations solver categories